Lily Marlene a Birkenau (Materiali di Estetica. Terza serie, 2025)
Inside the Birkenau extermination camp, a beautiful young Hungarian girl is known by the name of Lili because she can sing the famous song very well. Her beauty and her singing will become a death trap for her that she will not survive, despite the affection of the other prisoners. A negative empathy plays against her and introduces a cold wind also in the reader's relationship with this story.
Keywords: Birkenau; deportee; song; mud